Tactics and strategies to evade everyday racism by ‘black’ workers in Santiago de Chile - Cabello Valenzuela, Cristian Alexis (2019)
The objective of this article is to describe and analyze the practices of tactical and / or strategic use that "black" Latin American immigrants mobilize in different spaces of interaction in Chilean society. To do so, it discusses the concept of social practices and especially of tactics and strategies, following the proposals of De Certeau. Secondly, it analyzes the practices of resistance and the creation of transnational spaces that Afro Latin American immigrants develop. Finally, it concludes with the idea that although many “black” immigrants permanently live de-humanization situations in Chile (harassment, stigmatization, violence or exploitation), they manage to elaborate ways to facilitate their settlement in a racist and sexist society.